The EU fundamental rights policy as a source of euroscepticism - Leconte, Cécile (Human rights review, 2014)
This article analyzes how the development of the European Union (EU) fundamental rights policy feeds Euroscepticism—and notably political Euroscepticism—within segments of national political elites in EU Member States. More specifically, it argues that this relatively new policy also gives rise to a new form of political Euroscepticism, which has been defined as “value-based Euroscepticism,” e.g., the perception that the EU via its fundamental rights policy, unduly interferes in matters where value systems and core domestic preferences on ethical issues are at stake. This happens in a context where the EU is resented, by some segments of political elites, for allegedly empowering diverse groups (such as ethnic minorities, immigrants' associations, judges, and so on) at the expense of popular sovereignty. This resentment is exacerbated by the fact that national governments are increasingly submitted to the critical assessment of EU-level actors (e.g., the European Parliament or the European Commission) in terms of democratic credentials.